Outcomes of Dynamic Condylar Screw Fixation in Subtrochanteric Femoral Fractures - Azlan Bashir, Haider Ali, Zaigham Habib, Usman Amjad, Muhammad Abdul Shakoor, Armughan Ahmar, Syed Wasif Ali Shah (Pakistan Journal of Medical & Health Sciences, 2023)
Aim: To determine the union rate in subtrochanteric femoral fractures fixed with dynamic condylar screw system. Study Design: Descriptive study Place and duration of study: This study was conducted in the Department of Orthopaedic Surgery, Shaikh Zayed Hospital, Lahore from June 2019 to December 2021. Methodology: This study included 100 patients with subtrochanteric femoral fractures. Sampling was done with the consecutive sampling technique. Male and female patients were included in this study. The A.O classification was used to classify all the fractures. After 8 weeks, the fracture union was evaluated, and the results (in terms of yes/no) were documented on a pre-designed proforma. Results: This study included 100 patients with subtrochanteric femoral fractures. The patients’ average age was 39.56±15.125 years, and the average duration of fracture was 4.10±1.973 days. There were fifty nine female patients (59%), and forty one male patients (41%). Type A fractures were reported in 19(19%) patients, type B in 48 (48%) patients, and type C in 33 (33%). Fracture union was reported in 79 (79%) of the 100 cases. Dynamic condylar screw is regarded as a very good implant for subtrochanteric fractures due to numerous advantages such as ease of availability, stable fixation, increased strength, resistance to stress failure and reduced surgical time. However, the union rate in our local population was not known prior to our research. Therefore, the purpose of this study is to find the union rates in subtrochanteric femoral fractures fixed with dynamic condylar screw. Conclusion: The results of this study revealed an increased union rate in patients with subtrochanteric femoral fractures fixed with DCS (dynamic condylar screw system). There was a significant relationship between patient age, fracture duration, and fracture type. Keywords: Subtrochanteric Femoral Fractures, Internal Fixation, Dynamic Condylar Screw.